Aerodynamics analysis of superheated steam flow through multi-stage perforated plates. (October 2019) - Qian, Jin-yuan; Hou, Cong-wei; Wu, Jia-yi; Gao, Zhi-xin; Jin, Zhi-jiang
Highlights: Aerodynamics of superheated steam through perforated plates is investigated. Multi-stage perforated plate with different structural parameters is studied. Mach number analysis is carried out to find out the aerodynamics characteristics. Critical distance between two perforated plates is achieved. Abstract: Superheated steam is the main medium in the piping system of steam power plants. In these pipelines, perforated plates are widely used to regulate the flow rate, pressure, and also reduce aerodynamics noise of steam. For the superheated steam flow, the flow resistance and aerodynamic noise are two key parameters of the perforated plates. In order to investigate the flow resistance and steam aerodynamic characteristics, this paper presents a systematic study of superheated steam and water through multi-stage perforated plates under a wide range of operating conditions with both experimental and numerical methods. The experiments are conducted out to validate the applicability of the adopted numerical models. Then numerical methods are used to investigate the water flow resistance and the Mach number distributions of the steam flow with different structural parameters. The results show that with the increase of the holes diameter, the pressure drop decreases and the Mach number increases. Mach number drops significantly when the position of side holes moves towards the edge of the perforated plate. A critical stage distance is found, at which the pressure drop has the maximum value. Besides, the occurrence probability of supersonic steam flow increases as the decrease of stage distance under a restricted space, and the disturbed length of supersonic steam flow is longer when the stage distance is smaller. This work can be referred by someone who deals with perforated plate design in steam piping systems or related research topics.